2001
DOI: 10.1017/cbo9780511486500
|View full text |Cite
|
Sign up to set email alerts
|

Regularity in Semantic Change

Abstract: This important study of semantic change examines how new meanings arise through language use, especially the various ways in which speakers and writers experiment with uses of words and constructions in the flow of strategic interaction with addressees. There has been growing interest in exploring systemicities in semantic change from a number of perspectives including theories of metaphor, pragmatic inferencing, and grammaticalization. Like earlier studies, these have for the most part been based on data take… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
552
2
172

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 684 publications
(796 citation statements)
references
References 306 publications
19
552
2
172
Order By: Relevance
“…In Diewald's (2006) terms, (38) and (39) are 'isolating' contexts, in which the propositional reading has become associated with the construction as a distinct reading. From the discussion above, it can be concluded that the path followed by the appropriateness adjectives basically fits the customary A > A/B > B schema proposed by Traugott & Dasher (2002), in which A is the original use, B the new use and A/B the transitional use with features of both A and B. Applied to the constructions studied here, A is the mandative to-or that-complement, B the propositional to-or that-complement, and A/B the to-or that-complement which bridges from a mandative to a propositional reading.…”
Section: Adjectives Level Form Cemet Clmet1 Clmet2 Clmet3supporting
confidence: 56%
“…In Diewald's (2006) terms, (38) and (39) are 'isolating' contexts, in which the propositional reading has become associated with the construction as a distinct reading. From the discussion above, it can be concluded that the path followed by the appropriateness adjectives basically fits the customary A > A/B > B schema proposed by Traugott & Dasher (2002), in which A is the original use, B the new use and A/B the transitional use with features of both A and B. Applied to the constructions studied here, A is the mandative to-or that-complement, B the propositional to-or that-complement, and A/B the to-or that-complement which bridges from a mandative to a propositional reading.…”
Section: Adjectives Level Form Cemet Clmet1 Clmet2 Clmet3supporting
confidence: 56%
“…These have developed into a semantic contrast between 'a past event that is unknown to the addressee' (uúch) and 'a past event that is known to the addressee' (kuúch). Bergqvist (in press) details this development as an instance of "intersubjectification" (Traugott & Dasher, 2002). …”
Section: Resultsmentioning
confidence: 99%
“…The research is usage based both in the sense that it promotes investigation of "real" language use (such as spoken and written communication and experiments of different kinds) and with reference to the nature of language (i.e., how languages are acquired, how they develop and how they change in the contexts where they are used in social communication; cf. Traugott and Dasher 2005;Tomasello 2003Tomasello , 2008). People's ways of expressing themselves are functionally motivated and spring from communicational needs in social intercourse and the settings of the symbolic structures, i.e., the form-meaning pairings.…”
Section: Basic Assumptions and Theoretical Frameworkmentioning
confidence: 99%